PENYULUHAN HUKUM TENTANG BAHAYA PENYALAHGUNAAN NARKOTIKA DI SMP NEGERI 3 LABUHAN HAJI - R. Fahmi Natigor Daulay; Febrihadi Suparidho; Ade Sultan Muhammad; Muhammad Rifaldi Setiawan (JURNAL PENGABDIAN MANDIRI, 2025)
Drug abuse in Indonesia has become a serious threat that has spread not only in urban areas, but also to remote villages and school environments. Law Number 35 of 2009 concerning Narcotics defines narcotics as substances that can affect consciousness and the central nervous system, and have the potential to cause dependence. Lack of legal understanding and information about the impact of narcotics on health, social, and economic causes increased vulnerability of the community, especially students, to abuse of this illegal substance. One case that emerged was the arrest of a junior high school student in Purwakarta who was involved as a drug dealer. The case illustrates the urgency of early prevention through legal education among students, including at SMP Negeri 3 Labuhan Haji, East Lombok Regency. Effective prevention efforts involve education, strengthening the role of the family, creating a positive environment, and support from the government and law enforcement officers. Education about the dangers and legal sanctions of narcotics is an important step to save the younger generation from the threat of drugs for a better future